Topographic-anatomic peculiarities of the thoracic part of the trachea in human fetuses aged 4-6 months - Tatiana V. KHMARA; Igor I. ZAMORSKII; Oleg F. MARCHUK; Mariana A. RYZNYCHUK; Leonid V. SHVYHAR; Mariana I. KRYVCHANSKA; Violeta G. KHOMENKO (Archives of the Balkan Medical Union, 2019)
Introduction. Rapid development of perinatal medicine has led to an increase in the number of fetal surgical interventions performed intrauterine, on the trachea and principal bronchi. Therefore, topographic and anatomical peculiarities of the trachea and its morphometric parameters in the human fetuses of different ages cause interest of morphologists and surgeons.